2018
DOI: 10.1186/s12885-018-4887-3
|View full text |Cite
|
Sign up to set email alerts
|

Receptor activator of nuclear factor kB ligand, osteoprotegerin, and risk of death following a breast cancer diagnosis: results from the EPIC cohort

Abstract: BackgroundReceptor activator of nuclear factor kappa-B (RANK)-signaling is involved in tumor growth and spread in experimental models. Binding of RANK ligand (RANKL) to RANK activates signaling, which is inhibited by osteoprotegerin (OPG). We have previously shown that circulating soluble RANKL (sRANKL) and OPG are associated with breast cancer risk. Here we extend these findings to provide the first data on pre-diagnosis concentrations of sRANKL and OPG and risk of breast cancer-specific and overall mortality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 41 publications
0
12
0
1
Order By: Relevance
“…Sarink et al have recently conducted a large-scale prospective study on 2006 pre- and postmenopausal patients with incident invasive breast cancer participating in the EPIC (European Prospective Investigation into Cancer and Nutrition) cohort. Importantly, the authors showed that higher pre-diagnosis circulating OPG concentrations - assessed by an electrochemiluminescent assay - are associated with a greater risk of breast cancer-specific and overall mortality, especially in ER-positive breast cancer patients [137]. Similarly, Rachner et al showed that higher OPG serum levels - detected by ELISA - are associated with a significantly higher risk of death from breast cancer in patients with primary, non-metastatic breast cancer.…”
Section: Role Of Opg In Breast Tumorigenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Sarink et al have recently conducted a large-scale prospective study on 2006 pre- and postmenopausal patients with incident invasive breast cancer participating in the EPIC (European Prospective Investigation into Cancer and Nutrition) cohort. Importantly, the authors showed that higher pre-diagnosis circulating OPG concentrations - assessed by an electrochemiluminescent assay - are associated with a greater risk of breast cancer-specific and overall mortality, especially in ER-positive breast cancer patients [137]. Similarly, Rachner et al showed that higher OPG serum levels - detected by ELISA - are associated with a significantly higher risk of death from breast cancer in patients with primary, non-metastatic breast cancer.…”
Section: Role Of Opg In Breast Tumorigenesismentioning
confidence: 99%
“…quantitative PCR, immunohistochemistry). According to the recent findings from Sarink et al [137] and Rachner et al [138], it is also possible that OPG circulating concentrations at diagnosis represent a more informative measure for breast cancer prognosis and mortality than OPG expression in tumor tissue. Further investigations in well-defined patient cohorts (e.g.…”
Section: Role Of Opg In Breast Tumorigenesismentioning
confidence: 99%
“…Studies in experimental animal models have shown that the RANK axis plays an important role in a number of processes including bone turnover, immune response, cardiovascular disease, and breast development in pregnancy, as well as development and progression of breast cancer (1)(2)(3). With respect to breast cancer, we (4)(5)(6) and others (7)(8)(9)(10) have observed associations between circulating concentrations of RANK axis members and breast cancer risk and prognosis. Following development of an antibody for RANKL, denosumab, there is increasing interest in RANKL and OPG in relation to breast cancer prevention and treatment.…”
Section: Introductionmentioning
confidence: 97%
“…Another study identified high serum OPG levels to be mainly associated with increased risk for ER-BC (39). On the other hand, a large scale investigation with a cohort of 1,976 incident invasive BC cases, of which 1,598 were ER+, showed limited evidence for correlating circulating RANKL levels with BC risk (40). Notably, and despite the availability of a myriad of BC studies in the proteomics literature (41,42), the field is still lacking invalidated protein markers for both BC risk prediction and early detection.…”
Section: Circulating Proteinsmentioning
confidence: 99%